2010
DOI: 10.5194/bg-7-247-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonate ion concentration and irradiance on calcification in planktonic foraminifera

Abstract: Abstract.The 3 ] expected at the end of the century, the calcification rates of these two species are projected to be 6 to 13% lower than the present conditions, while the final shell weights are reduced by 20 to 27% for O. universa and by 4 to 6% for G. sacculifer. These results indicate that ocean acidification would impact on calcite production by foraminifera and may decrease the calcite flux contribution from these organisms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 40 publications
3
96
0
Order By: Relevance
“…It is concluded that carbonate ion concentration is the parameter influencing growth rate in Ammonia sp. This conclusion tallies with response patterns of other species studied (Manno et al, 2012;Lombard et al, 2010;Russell et al, 2004;Kuroyanagi et al, 2009;Bijma et al, 2002). However, all of the latter studies, with the exception of the one by Bijma et al (2002), employed either DIC-manipulation or TA-manipulation methods and could therefore not identify a single parameter responsible for observed adverse effects.…”
Section: Growth Ratementioning
confidence: 68%
“…It is concluded that carbonate ion concentration is the parameter influencing growth rate in Ammonia sp. This conclusion tallies with response patterns of other species studied (Manno et al, 2012;Lombard et al, 2010;Russell et al, 2004;Kuroyanagi et al, 2009;Bijma et al, 2002). However, all of the latter studies, with the exception of the one by Bijma et al (2002), employed either DIC-manipulation or TA-manipulation methods and could therefore not identify a single parameter responsible for observed adverse effects.…”
Section: Growth Ratementioning
confidence: 68%
“…SEM imaging, while an effective way of distinguishing O. universa genotypes (Morard et al, 2009), is destructive to the shell and does not allow for subsequent geochemical analysis. The ρ A methods provides a nondestructive means by which O. universa genotypes can be distinguished (Bé et al, 1973;Lea et al, 1995;Barker and Elderfield, 2002;Schmidt et al, 2004;Lombard et al, 2009Lombard et al, , 2010Marshall et al, 2013), these factors do not appear to inhibit the identification of thin and thick O. universa morphotypes using the methods presented in this study. If only a single morphotype exists in a given sample, it is possible to assign an O. universa specimen to a morphotype by comparing its mean weight, area and ρ A to the ranges exhibited by thick and thin morphotypes in a given study area ( Fig.…”
Section: Morphotype Identificationmentioning
confidence: 99%
“…Size variations in the final spherical chamber of O. universa have been linked to changes in calcification temperature (Schmidt et al, 2004;Lombard et al, 2009), whereas thickness variations have been associated with changes in the carbonate ion concentration ([CO 3 2− ]) and variations in water column irradiance (related to symbiont photosynthesis; Lea et al, 1995;Lombard et al, 2010;Spero et al, 2015). Porosity variations in O. universa specimens have been attributed to changes in oxygen concentrations, such that porosity increases as oxygen concentrations decrease (Colombo and Cita, 1980).…”
Section: Orbulina Universa: Life Cycle Habitat Preferences and Morphmentioning
confidence: 99%
“…Most evidence suggests that the ability of many marine calcifying organisms to form carbonate skeletons and shells may be reduced with increasing seawater acidification including some (but not all) species of coccolithophores, corals, pteropods and foraminifera (e.g. Orr et al, 2005;Moy et al, 2009;Lombard et al, 2010;Beaufort et al, 2011;Andersson and Gledhill, 2013). Since phytoplankton are extremely sensitive to global environmental change (Litchman et al, 2012) all predicted changes in marine environmental conditions are likely to modify the abundance, composition and distribution of phytoplankton communities.…”
Section: Background and Objectivesmentioning
confidence: 99%